Evaluation of protein adsorption in rats submitted to nanotextured and polyurethane foam-coated silicone mini-implants - Eduardo Nascimento Silva; Gisela Hobson Pontes; Bárbara Zanon da Luz; Adriana Yuriko Koga; Lydia Masako Ferreira; Leandro Cavalcante Lipinski (Revista Brasileira de Cirurgia Plástica)
Introduction: The control of protein absorption is necessary to define biomaterials' properties and their specific uses. Blood plasma contains several different proteins, including fibrinogen, which plays an important role in cell adhesion and biocompatibility results in implants. This study's objectives were to evaluate in the laboratory rats subjected to the placement of nano-textured silicone mini-implants and polyurethane foam-coated mini-implants based on the measurement of serum fibrinogen and plasma proteins. Methods: Sixty albino rats were used, divided into two groups of 30 animals for each type of silicone mini-implant (nanotextured and polyurethane foam) and subdivided into three subgroups, according to the animals' euthanasia time (30, 60 and 90 days). The mini-implants were inserted in the animals' backs below the Panniculus carnosus. At the time of euthanasia, blood samples were obtained by cardiac puncture. The thermal precipitation technique was used to determine total and serum plasma proteins, and the difference between the latter two obtained the fibrinogen value. Results: When the groups were compared, it was observed that the nanotextured group presented a higher amount of fibrinogen and plasma protein in the 90-day subgroup, with statistical significance (p=0.004). When comparing the subgroups among themselves, a significant difference was evidenced (p<0.001). Conclusion: The nanotextured miniimplants showed a lower protein absorption concerning polyurethane foam-coated implants in the 90-day subgroup.